Ocena wiedzy uczniów warszawskich szkół średnich na temat skutków zdrowotnych wynikających z nadmiernego korzystania z promieniowania ultrafioletowego (UV) = Knowledge assessment about health effects caused by excessive use of ultraviolet radiation (UV) among high school students in Warsaw - Paweł Koczkodaj; Maria Sobol; Anna Maria Badowska-Kozakiewicz (Kazimierz Wielki University, 2016)
Koczkodaj Pawel, Sobol Maria, Badowska-Kozakiewicz Anna Maria. Ocena wiedzy uczniów warszawskich szkół średnich na temat skutków zdrowotnych wynikających z nadmiernego korzystania z promieniowania ultrafioletowego (UV) = Knowledge assessment about health effects caused by excessive use of ultraviolet radiation (UV) among high school students in Warsaw. Journal of Education, Health and Sport. 2016;6(5):94-110. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51293 http://ojs.ukw.edu.pl/index.php/johs/article/view/3512     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 10.05.2016.     Ocena wiedzy uczniów warszawskich szkół średnich na temat skutków zdrowotnych wynikających z nadmiernego korzystania z promieniowania ultrafioletowego (UV)   Knowledge assessment about health effects caused by excessive use of ultraviolet radiation (UV) among high school students in Warsaw   Paweł Koczkodaj1, Maria Sobol2, Anna Maria Badowska-Kozakiewicz3 Pawel Koczkodaj1, Maria Sobol2, Anna Maria Badowska-Kozakiewicz3   Zakład Biofizyki i Fizjologii Człowieka, Warszawski Uniwersytet Medyczny Department of Human Biophysics and Physiology, Medical University of Warsaw   Słowa kluczowe: promieniowanie ultrafioletowe (UV), choroby skóry, czerniak, profilaktyka, edukacja zdrowotna. Key words: ultraviolet radiation (UV), skin diseases, melanoma, prevention, health education.   Streszczenie 1. Wprowadzenie i cel pracy Promieniowanie ultrafioletowe jest obecne w codziennym życiu każdego człowieka. Stale rosnąca liczba nowych przypadków nowotworów złośliwych skóry w Polsce i na świecie może sugerować brak odpowiedniej wiedzy w zakresie fotoprotekcji. Podnoszenie świadomości społecznej, szczególnie wśród młodych ludzi, odnośnie skutków zdrowotnych nadmiernego działania promieniowania UV, pełni kluczową rolę w odniesieniu do ich obecnego i przyszłego stanu zdrowia. Celem przeprowadzonego badania była ocena poziomu wiedzy uczniów warszawskich szkół średnich na temat skutków zdrowotnych wynikających z nadmiernego korzystania z promieniowania ultrafioletowego, a także poznanie zachowań zdrowotnych młodych osób podczas korzystania z promieniowania UV. 2. Materiał i metodyka Zbadano 153 uczniów warszawskich szkół średnich. Rozkład płci był losowy, przedział wiekowy badanych wynosił od 17 do 19 lat. Badanie zostało przeprowadzone przy pomocy autorskiego kwestionariusza w wersji papierowej, składającego się z 29 pytań. Do zbadania związku między wybranymi cechami został zastosowany test niezależności chi-kwadrat (χ2) (pakiet STATISTICA12). W testach przyjęto poziom istotności p≤0,05. W zależności od liczebności zastosowano właściwe poprawki do testu chi-kwadrat. 3. Wyniki i wnioski Nie wystąpiła zależność pomiędzy takimi cechami jak: korzystanie z urządzeń opalających i postrzeganie poparzenia skóry jako czynnika kancerogennego, korzystanie z solarium i regularne przeglądanie znamion barwnikowych, wystąpienie czerniaka złośliwego skóry w przeszłości w rodzinie i korzystanie z urządzeń opalających, wystąpienie poparzenia skóry i częstość stosowania preparatów z filtrem UV. Powyższe wyniki mogą świadczyć o niekompletności wiedzy ankietowanych w zakresie wpływu UV na zdrowie człowieka.   Abstract 1. Introduction and aim Ultraviolet radiation is present in the daily life of every human being. The constantly growing number of new cases of skin cancer in Poland and in the world can suggest a lack of adequate knowledge of photoprotection. Raising public awareness, especially among young people about the health effects of excessive UV radiation use, plays a key role in relation to their current and future health. The aim of the study was to assess the level of knowledge among high school students in Warsaw about the health effects resulting from excessive use of ultraviolet radiation, as well as knowledge concerning health behaviors of young people using UV radiation. 2. Material and methods The study group consists of 153 students from Warsaw high schools. The gender distribution was random, the age range of the respondents was 17 to 19 years. The study was conducted using paper questionnaire, consisting of 29 questions. To examine the relationship between the selected traits has been applied test of independence chi-square (χ2) (STATISTICA12 package). In tests the level of significance was p≤0.05. Depending on the size used appropriate amendments to the chi-square test. 3. Results and conclusions There was no relationship between such features as: the use of tanning devices and perception of skin burns as a carcinogenic factor, the use of the solarium and regularly reviewing pigmented moles, the occurrence of malignant melanoma of the skin in the past in the family and the use of tanning devices, the occurrence of skin burns and frequency of use of formulations with UV protection. This may indicate incomplete knowledge of the respondents in terms of the impact of UV on human health.